Quasi-3D visualization and local parameter measurement of horizontal and nearly horizontal liquid–liquid two-phase flows by using PLIF method. (23rd November 2022) - Zhai, Lusheng; Meng, Xinyu; Meng, Zihan; Wang, Wenhao; Jin, Ningde
Highlights: A novel PLIF-60 system is designed to detect the flow structures at the radial section of the pipe. The corrected flow images are used to reconstruct the quasi-3D structures of liquid–liquid stratified interfaces and entrained droplets. The evolution of the interface structures and the spatial distributions of droplets are studied. Local aqueous phase holdup and droplet entrainment ratios are extracted based on the quasi-3D flow visualizations. The effects of flow conditions and pipe inclinations on the profiles of the aqueous phase holdup and the droplet entrainment ratio are uncovered. Abstract: Horizontal and nearly horizontal liquid–liquid two-phase flows are widely encountered in petroleum, chemical, and other important industrial production fields. The three-dimensional (3D) flow visualization and the local parameter measurement are of great significance for understanding the flow dynamics and revealing the flow-pattern transition mechanism. In this paper, experiments of horizontal and nearly horizontal (+5°) liquid–liquid flow are carried out in an acrylic pipe with an inner diameter of 20 mm. Silicone oil (organic phase) and water/glycerol mixture (aqueous phase) are used as the test fluid. A novel planar laser-induced fluorescence (PLIF) system is designed to detect the flow structures. The incident direction of the laser sheet is along the radial section of the pipe, and the PLIF camera is positioned at 60° to the plane of the laser sheet, referred to as PLIF-60. In the experiment, the two-dimensional (2D) flow images at the pipe radial section are captured by the PLIF-60 system. Considering the effect of the angle between the laser sheet and the PLIF camera, the flow images are corrected to remove the horizontal and vertical distortions. The liquid–liquid stratified interface and the entrained droplets are identified in the corrected flow images. A droplet tracking method is proposed to derive the droplet diameter and its quantity distribution. Quasi-3D flow structures are reconstructed upon the accurate detection of the stratified interface and the entrained droplets. The evolution characteristics of the interface structures and the spatial distributions of droplets are studied. In addition, aqueous phase holdup and droplet entrainment ratios at pipe axial and radial sections are extracted based on the quasi-3D flow visualizations. The effects of the flow conditions and the pipe inclinations on the profiles of the aqueous phase holdup and the droplet entrainment ratio are uncovered.